Methodological aspects of developing motor skills in children of different ages during football club activities - Grygus, Igor; Gamma, Tetiana; Godlevskyi, Petro; Zhuk, Mykhailo; Zukow, Walery (Journal of Education, Health and Sport, 2024)
The aim of the study is to examine methodological aspects of developing motor skills in children of different ages during football club activities. The article thoroughly explores training approaches for various age groups: preschool age (4-6 years), primary school age (7-10 years), middle school age (11-14 years), and adolescence (15-18 years). It is determined that each age group requires an individualized approach, taking into account anatomical and physiological characteristics and sensitive periods of children’s development. The development of motor skills is achieved through various game exercises, comprehensive physical training, tactical preparation, and innovative technologies. The article also emphasizes the importance of psychological support and individualized training programs for older age groups.